Multiple infections, relatedness and virulence in the anther‐smut fungus castrating Saponaria plants - Taiadjana M. Fortuna; Alice Namias; Alodie Snirc; Antoine Branca; Michael E. Hood; Christian Raquin; Jacqui A. Shykoff; Tatiana Giraud (Molecular Ecology, 2018)
Multiple infections (co‐occurrence of multiple pathogen genotypes within an individual host) can have important impacts on diseases. Relatedness among pathogens can affect the likelihood of multiple infections and their consequences through kin selection. Previous studies on the castrating anther‐smut fungus Microbotryum lychnidis‐dioicae have shown that multiple infections occur in its host plant Silene latifolia . Relatedness was high among fungal genotypes within plants, which could result from competitive exclusion between unrelated fungal genotypes, from population structure or from interactions between plant and fungal genotypes for infection ability. Here, we aimed at disentangling these hypotheses using M. saponariae and its host Saponaria officinalis , both experimentally tractable for these questions. By analysing populations using microsatellite markers, we also found frequent occurrence of multiple infections and high relatedness among strains within host plants. Infections resulting from experimental inoculations in the greenhouse also revealed high relatedness among strains co‐infecting host plants, even in clonally replicated plant genotypes, indicating that high relatedness within plants did not result merely from plant x fungus interactions or population structure. Furthermore, hyphal growth in vitro was affected by the presence of a competitor growing nearby and by its genetic similarity, although this latter effect was strain‐dependent. Altogether, our results support the hypothesis that relatedness‐dependent competitive exclusion occurs in Microbotryum fungi within plants. These microorganisms can thus respond to competitors and to their level of relatedness.

Widespread selective sweeps throughout the genome of model plant pathogenic fungi and identification of effector candidates - H. Badouin; P. Gladieux; J. Gouzy; S. Siguenza; G. Aguileta; A. Snirc; S. Le Prieur; C. Jeziorski; A. Branca; T. Giraud (Molecular Ecology, 2017)
Identifying the genes underlying adaptation, their distribution in genomes and the evolutionary forces shaping genomic diversity are key challenges in evolutionary biology. Very few studies have investigated the abundance and distribution of selective sweeps in species with high‐quality reference genomes, outside a handful of model species. Pathogenic fungi are tractable eukaryote models for investigating the genomics of adaptation. By sequencing 53 genomes of two species of anther‐smut fungi and mapping them against a high‐quality reference genome, we showed that selective sweeps were abundant and scattered throughout the genome in one species, affecting near 17% of the genome, but much less numerous and in different genomic regions in its sister species, where they left footprints in only 1% of the genome. Polymorphism was negatively correlated with linkage disequilibrium levels in the genomes, consistent with recurrent positive and/or background selection. Differential expression in planta and in vitro, and functional annotation, suggested that many of the selective sweeps were probably involved in adaptation to the host plant. Examples include glycoside hydrolases, pectin lyases and an extracellular membrane protein with CFEM domain. This study thus provides candidate genes for being involved in plant–pathogen interaction (effectors), which have remained elusive for long in this otherwise well‐studied system. Their identification will foster future functional and evolutionary studies, in the plant and in the anther‐smut pathogens, being model species of natural plant–pathogen associations. In addition, our results suggest that positive selection can have a pervasive impact in shaping genomic variability in pathogens and selfing species, broadening our knowledge of the occurrence and frequency of selective events in natural populations.

Lower prevalence but similar fitness in a parasitic fungus at higher radiation levels near Chernobyl - Gabriela Aguileta; Helene Badouin; Michael E. Hood; Anders P. Møller; Stephanie Le Prieur; Alodie Snirc; Sophie Siguenza; Timothy A. Mousseau; Jacqui A. Shykoff; Christina A. Cuomo; Tatiana Giraud (Molecular Ecology, 2016)
Nuclear disasters at Chernobyl and Fukushima provide examples of effects of acute ionizing radiation on mutations that can affect the fitness and distribution of species. Here, we investigated the prevalence of Microbotryum lychnidis‐dioicae , a pollinator‐transmitted fungal pathogen of plants causing anther‐smut disease in Chernobyl, its viability, fertility and karyotype variation, and the accumulation of nonsynonymous mutations in its genome. We collected diseased flowers of Silene latifolia from locations ranging by more than two orders of magnitude in background radiation, from 0.05 to 21.03 μGy/h. Disease prevalence decreased significantly with increasing radiation level, possibly due to lower pollinator abundance and altered pollinator behaviour. Viability and fertility, measured as the budding rate of haploid sporidia following meiosis from the diploid teliospores, did not vary with increasing radiation levels and neither did karyotype overall structure and level of chromosomal size heterozygosity. We sequenced the genomes of twelve samples from Chernobyl and of four samples collected from uncontaminated areas and analysed alignments of 6068 predicted genes, corresponding to 1.04 × 10 7 base pairs. We found no dose‐dependent differences in substitution rates (neither dN , dS , nor dN / dS ). Thus, we found no significant evidence of increased deleterious mutation rates at higher levels of background radiation in this plant pathogen. We even found lower levels of nonsynonymous substitution rates in contaminated areas compared to control regions, suggesting that purifying selection was stronger in contaminated than uncontaminated areas. We briefly discuss the possibilities for a mechanistic basis of radio resistance in this nonmelanized fungus.

The population biology of fungal invasions - P. Gladieux; A. Feurtey; M. E. Hood; A. Snirc; J. Clavel; C. Dutech; M. Roy; T. Giraud (Molecular Ecology, 2015)
Fungal invasions are increasingly recognized as a significant component of global changes, threatening ecosystem health and damaging food production. Invasive fungi also provide excellent models to evaluate the generality of results based on other eukaryotes. We first consider here the reasons why fungal invasions have long been overlooked: they tend to be inconspicuous, and inappropriate methods have been used for species recognition. We then review the information available on the patterns and mechanisms of fungal invasions. We examine the biological features underlying invasion success of certain fungal species. We review population structure analyses, revealing native source populations and strengths of bottlenecks. We highlight the documented ecological and evolutionary changes in invaded regions, including adaptation to temperature, increased virulence, hybridization, shifts to clonality and association with novel hosts. We discuss how the huge census size of most fungi allows adaptation even in bottlenecked, clonal invaders. We also present new analyses of the invasion of the anther‐smut pathogen on white campion in North America, as a case study illustrating how an accurate knowledge of species limits and phylogeography of fungal populations can be used to decipher the origin of invasions. This case study shows that successful invasions can occur even when life history traits are particularly unfavourable to long‐distance dispersal and even with a strong bottleneck. We conclude that fungal invasions are valuable models to contribute to our view of biological invasions, in particular by providing insights into the traits as well as ecological and evolutionary processes allowing successful introductions.

Inference of domestication history and differentiation between early‐ and late‐flowering varieties in pearl millet - Y. Dussert; A. Snirc; T. Robert (Molecular Ecology, 2015)
Pearl millet ( Pennisetum glaucum ) is a staple crop in Sahelian Africa. Farmers usually grow varieties with different cycle lengths and complementary functions in Sahelian agrosystems. Both the level of genetic differentiation of these varieties and the domestication history of pearl millet have been poorly studied. We investigated the neutral genetic diversity and population genetic structure of early‐ and late‐flowering domesticated and wild pearl millet populations using 18 microsatellite loci and 8 nucleotide sequences. Strikingly, early‐ and late‐flowering domesticated varieties were not differentiated over their whole distribution area, despite a clear difference in their isolation‐by‐distance pattern. Conversely, our data brought evidence for two well‐differentiated genetic pools in wild pearl millet, allowing us to test scenarios with different numbers and origins of domestication using approximate Bayesian computation ( ABC ). The ABC analysis showed the likely existence of asymmetric migration between wild and domesticated populations. The model choice procedure indicated that a single domestication from the eastern wild populations was the more likely scenario to explain the polymorphism patterns observed in cultivated pearl millet.

Corrigendum - Y. Dussert; M.‐S. Remigereau; M. C. Fontaine; A. Snirc; G. Lakis; S. Stoeckel; T. Langin; A. Sarr; T. Robert (Molecular Ecology, 2013)

Polymorphism pattern at a miniature inverted‐repeat transposable element locus downstream of the domestication gene Teosinte‐branched1 in wild and domesticated pearl millet - Y. Dussert; M.‐S. Remigereau; M. C. Fontaine; A. Snirc; G. Lakis; S. Stoeckel; T. Langin; A. Sarr; T. Robert (Molecular Ecology, 2013)
Unravelling the mechanisms involved in adaptation to understand plant morphological evolution is a challenging goal. For crop species, identification of molecular causal polymorphisms involved in domestication traits is central to this issue. Pearl millet, a domesticated grass mostly found in semi‐arid areas of Africa and India, is an interesting model to address this topic: the domesticated form shares common derived phenotypes with some other cereals such as a decreased ability to develop basal and axillary branches in comparison with the wild phenotype. Two recent studies have shown that the orthologue of the maize gene Teosinte‐Branched1 in pearl millet ( PgTb1 ) was probably involved in branching evolution during domestication and that a miniature inverted‐repeat transposable element ( MITE ) of the Tuareg family was inserted in the 3′ untranslated region of PgTb1 . For a set of 35 wild and domesticated populations, we compared the polymorphism patterns at this MITE and at microsatellite loci. The Tuareg insertion was nearly absent in the wild populations, whereas a strong longitudinal frequency cline was observed in the domesticated populations. The geographical pattern revealed by neutral microsatellite loci clearly demonstrated that isolation by distance does not account for the existence of this cline. However, comparison of population differentiation at the microsatellite and the MITE loci and analyses of the nucleotide polymorphism pattern in the downstream region of PgTb1 did not show evidence that the cline at the MITE locus has been shaped by selection, suggesting the implication of a neutral process. Alternative hypotheses are discussed.